2020
DOI: 10.1002/ejhf.1902
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the inflammatory‐metabolic phenotype of heart failure with a preserved ejection fraction: a hypothesis to explain influence of sex on the evolution and potential treatment of the disease

Abstract: Accumulating evidence points to the existence of an inflammatory-metabolic phenotype of heart failure with a preserved ejection fraction (HFpEF), which is characterized by biomarkers of inflammation, an expanded epicardial adipose tissue mass, microvascular endothelial dysfunction, normal-to-mildly increased left ventricular volumes and systolic blood pressures, and possibly, altered activity of adipocyte-associated inflammatory mediators. A broad range of adipogenic metabolic and systemic inflammatory disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 273 publications
(467 reference statements)
8
109
0
3
Order By: Relevance
“…Independently on the cause-consequence relationship between SUA and MS, the presence of SUA in patients with MS seems to mark a greater risk of CVM. Indeed, animal models have shown that decreasing uric acid levels can prevent or reverse MS features [20], probably because hyperuricemia can induce endothelial dysfunction [21] and/or oxidative changes in adipocytes [22], which are typical stigmata of MS. Interestingly, all these features are increasingly described in HF with preserved ejection fraction (HFpEF), pointing to the existence of an inflammatory-metabolic phenotype [23]. A recent subanalysis from the PARAGON-HF trial demonstrated that hyperuricaemia was associated with an increased risk of adverse cardiovascular outcomes (CVM and HF hospitalisation) [24], suggesting that SUA may be a relevant therapeutic target also in HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…Independently on the cause-consequence relationship between SUA and MS, the presence of SUA in patients with MS seems to mark a greater risk of CVM. Indeed, animal models have shown that decreasing uric acid levels can prevent or reverse MS features [20], probably because hyperuricemia can induce endothelial dysfunction [21] and/or oxidative changes in adipocytes [22], which are typical stigmata of MS. Interestingly, all these features are increasingly described in HF with preserved ejection fraction (HFpEF), pointing to the existence of an inflammatory-metabolic phenotype [23]. A recent subanalysis from the PARAGON-HF trial demonstrated that hyperuricaemia was associated with an increased risk of adverse cardiovascular outcomes (CVM and HF hospitalisation) [24], suggesting that SUA may be a relevant therapeutic target also in HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…Besides RA, no other SCTD is currently incorporated into any widely accepted CVD risk calculators 2 . This is not appropriate approach, as accelerated atherosclerosis and heart failure coexist in all distinct phenotypes of SCTD 5,32,34,36 . The mechanisms that contribute to accelerated atherosclerosis are still incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that SCTDs are commonly associated with heart failure preserved ejection fraction (HFpEF) and pulmonary hypertension (PH), 5,6 increasing the risk of death by almost twofold 7 . The synergy amongst HFpEF, systemic inflammatory disorders and atherosclerosis represents a vicious circle leading to very poor survival 5 . As systemic inflammation precedes the onset of HFpEF and atherosclerosis by years, 8 it would be beneficial to conduct early risk prediction in order to prevent future adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the inflammatory-metabolic phenotype of HFpEF, which is characterized by biomarkers of inflammation, an expanded epicardial adipose tissue mass, microvascular endothelial dysfunction, increased left ventricular volumes and systolic blood pressures, and possibly, altered activity of adipocyteassociated inflammatory mediators is primarily seen in women. 81 Therefore, sex differences in cardiac structure, function and metabolism, vascular ageing, and immune system biology are considerable. Future research initiatives of potential sex-specific mechanisms in HFpEF may provide important insights for the optimal prevention and management of HFpEF in both women and men.…”
Section: Sex Differences In Hfpefmentioning
confidence: 99%